A rationally-engineered IL-2 improves the antitumor effect of anti-CD20 therapy. (1st January 2020) - Casadesús, Ana Victoria; Deligne, Claire; Diallo, Béré Kadjdiatou; Sosa, Katya; Josseaume, Nathalie; Mesa, Circe; León, Kalet; Hernández, Tays; Teillaud, Jean-Luc
ABSTRACT: Anti-CD20 treatment represents a therapeutic benefit for patients with B-cell lymphomas, although more efficient therapies are needed for refractory or relapsing patients. Among them, the combination of anti-CD20 and IL-2 that induces T cell response has been hampered by the expansion of FoxP3 + Tregs that strongly express the high affinity IL-2 receptor (IL-2R αβγ). We explore here the anti-tumor effect of an anti-CD20 antibody combined with a mutated IL-2 (no-alpha mutein) which has a disrupted affinity for the IL-2R αβγ. We demonstrate that anti-CD20/no-alpha mutein combination significantly augments the survival rate of mice challenged with huCD20 + cells as compared to animals treated with anti-CD20 ± IL-2. Moreover, the combination with no-alpha mutein but not IL-2 provokes an increase of granzyme B and perforin in splenic NK and CD8 + T cells, a reduction of Tregs and an increase in activated macrophages. The former combination also induces a T helper profile different from that obtained with IL-2, with an earlier polarization to Th1 and no increase in Th17. The therapeutic effect of anti-CD20/no-alpha mutein was accompanied by an expansion of peripheral central (TCM) and effector (TEM) memory CD8 + T cell compartments. Last, as opposed to IL-2, no-alpha mutein administered at the beginning of anti-CD20 treatment did not dampen the long-term protection of surviving mice after tumor rechallenge. Thus, this study shows that the combination of anti-tumor antibodies and no-alpha mutein is a promising approach to improve the therapeutic effect of these antibodies by potentiating NK/macrophage-mediated innate immunity and the adaptive T-cell response.